Final catcall - Kelly, Sofie, 1958- (Kelly, Sofie, 1958- Magical cats mystery., 2013)
When Hugh Davis, the director of a local theater festival, is found shot, leaving behind evidence of blackmail and fraud, Kathleen Paulson and her cats try to catch the killer.